Therapeutic Engagement and Treatment Progress: Developing and Testing an In-Treatment Measure of Client Engagement Among Sex Offenders in a Group Program. (December 2019) - Frost, Andrew; Grace, Randolph C.; McLean, Anthony P.
The engagement process of sexual offenders in group-based cognitive-behavioral treatment is an important area of study. Disclosure management style (DMS), a model developed from grounded-theory research of men undertaking a prototypical program, provides a framework to assess engagement in treatment. Our goal was to develop a quantitative measure of DMS, to test its reliability and validity, and to evaluate its utility as a measure of treatment progress by examining relationships between DMS and established measures of treatment change. We studied a sample of men ( N = 93) who undertook an intensive prison-based treatment program in New Zealand. Variables included DMS measures, psychometric measures of dynamic risk and treatment change, static risk, clinician rating of treatment progress, and recidivism outcomes. We found that (a) DMS shows an acceptable level of agreement between independent raters, (b) DMS-based ratings of engagement changed over the course of treatment and were correlated with measures of change based on offender self-reports, and (c) offenders showed heterogeneity in terms of their trajectories of change as assessed by DMS ratings.